Combined cross-sectional and tangential margin evaluation of different tumor types in dogs and cats - Vincenti, Simona; Aeschlimann, Leonore; Brunner, Anna; Vidondo, Beatriz; Wavreille, Vincent; Bicanova, Ludmila; Soto, Sara (Frontiers in Veterinary Science, 2025)
IntroductionHistological evaluation of tumors involves tumor diagnosis and assessment of surgical margins to determine whether they are free (clean) or infiltrated (dirty) by neoplastic cells. In veterinary medicine, cross-sectioning is most commonly used to trim tumors. It is simple, inexpensive, and allows to measure histologic tumor-free distances (HTFD). However, only a minimal portion of the surgical margins are assessed, potentially missing dirty margins. Tangential sectioning evaluates the entire surgical excision border, minimizing the risk of missing dirty margins, but it is more time-consuming, more expensive and HTFD cannot be measured. No study has yet compared these two trimming techniques on different tumors in cats and dogs. Consequently, the main goal of our study was to compare the two trimming techniques and evaluate their agreement.MethodsWe performed both trimming methods and evaluated these parameters in 20 tumors from 13 dogs and 6 cats, on which curative-intent surgical excision was performed. Kappa statistics were calculated to measure agreement between margin evaluation with the two methods.ResultsCross-sectioning detected dirty margins in 1/20 (5%) tumors. Tangential sectioning identified 11/20 (55%) tumors with dirty surgical margins, including the one detected with the cross-sectioning method (kappa = 0.0826). Ten tumors with dirty margins with the tangential method were not detected as dirty with the cross-sectioning method. Thus, cross sectioning presented a total of 50% false-negative (dirty margins identified as clean margins). The tangential trimming needed a higher number of cassettes and time required for trimming and evaluation.ConclusionBased on these results, despite the higher costs, we recommend using a combination of cross and tangential trimming for tumors in cats and dogs.